Atrioventricular 2 : 1 block as clinical presentation of a septal mass causing left ventricular outflow tract obstruction. (January 2015) - Brunetti, Natale D.; Correale, Michele; Ieva, Riccardo; De Gennaro, Luisa; Pellegrino, Pier L.; Cuculo, Andrea; Di Biase, Matteo
Abstract : We report the case of a 56-year-old woman with effort angina, dyspnea and a septal mass causing atrioventricular block, treated with pacemaker implantation, and left ventricular outflow tract obstruction (induced by septal mass protrusion into left ventricular cavity).